A new approach to off-gas analysis for shaken bioreactors showing high CTR and RQ accuracy - Andreas Schulte; Janik Brockmann; Nina Müller; Tibor Anderlei; Jochen Büchs (Journal of Biological Engineering)
Abstract Background Shake flasks are essential tools in biotechnological development due to their cost efficiency and ease of use. However, a significant challenge is the miniaturization of process analytical tools to maximize information output from each cultivation. This study aimed to develop a respiration activity online measurement system via off-gas analysis, named “Transfer rate Online Measurement” (TOM), for determining the oxygen transfer rate (OTR), carbon dioxide transfer rate (CTR), and the respiration quotient (RQ) in surface-aerated bioreactors, primarily targeting shake flasks. Results Sensors for off-gas analysis were placed in a bypass system that avoids the shaking of the electronics and sensors. An electrochemical oxygen sensor and an infrared CO2 sensor were used. The bypass system was combined with the established method of recurrent dynamic measurement phases, evaluating the decrease in oxygen and the increase in CO2 during stopped aeration. The newly developed measurement system showed high accuracy, precision and reproducibility among individual flasks, especially regarding CTR measurement. The system was compared with state-of-the-art RAMOS technology (Respiration Activity Monitoring System, see explanation below) and calibrated with a non-biological model system. The accuracy of RQ measurement was +-4% for the tested range (8% filling volume, OTR and CTR: 0–56 mmol/L/h), allowing for the determination of metabolic switches and quantitative analysis of metabolites. At ambient CO2 levels, a CTR resolution of less than 0.01 mmol/L/h was possible. The system was applied to the microbial model systems S. cerevisiae, G. oxydans, and E. coli. Physiological states, such as growth vs. protein production, could be revealed, and quantitative analysis of metabolites was performed, putting focus on RQ measurements. Conclusions The developed TOM system showcases a novel approach to measuring OTR, CTR, and RQ in shaken bioreactors. It offers a robust and accurate solution for respiration activity analysis. Due to its flexible design and tunable accuracy, it enables measurement in various applications and different shake flasks.